Heterozygous deletion of Gpr55 does not affect a hyperthermia-induced seizure, spontaneous seizures or survival in the Scn1a+/- mouse model of Dravet syndrome - Lyndsey L. Anderson; Dilara A. Bahceci; Nicole A. Hawkins; Declan Everett-Morgan; Samuel D. Banister; Jennifer A. Kearney; Jonathon C. Arnold (PLoS ONE, 2023)
A purified preparation of cannabidiol (CBD), a cannabis constituent, has been approved for the treatment of intractable childhood epilepsies such as Dravet syndrome. Extensive pharmacological characterization of CBD shows activity at numerous molecular targets but its anticonvulsant mechanism(s) of action is yet to be delineated. Many suggest that the anticonvulsant action of CBD is the result of G protein-coupled receptor 55 (GPR55) inhibition. Here we assessed whether Gpr55 contributes to the strain-dependent seizure phenotypes of the Scn1a+/- mouse model of Dravet syndrome. The Scn1a+/- mice on a 129S6/SvEvTac (129) genetic background have no overt phenotype, while those on a [129 x C57BL/6J] F1 background exhibit a severe phenotype that includes hyperthermia-induced seizures, spontaneous seizures and reduced survival. We observed greater Gpr55 transcript expression in the cortex and hippocampus of mice on the seizure-susceptible F1 background compared to those on the seizure-resistant 129 genetic background, suggesting that Gpr55 might be a genetic modifier of Scn1a+/- mice. We examined the effect of heterozygous genetic deletion of Gpr55 and pharmacological inhibition of GPR55 on the seizure phenotypes of F1.Scn1a+/- mice. Heterozygous Gpr55 deletion and inhibition of GPR55 with CID2921524 did not affect the temperature threshold of a thermally-induced seizure in F1.Scn1a+/- mice. Neither was there an effect of heterozygous Gpr55 deletion observed on spontaneous seizure frequency or survival of F1.Scn1a+/- mice. Our results suggest that GPR55 antagonism may not be a suitable anticonvulsant target for Dravet syndrome drug development programs, although future research is needed to provide more definitive conclusions.